Memorizing the Qur'an: the Fast and Precise Way with the Talaqqi Method - Fahri Luthfi Ardiansyah; Gita Andini; Karin Nurahmah; Imam Tabroni (International Journal of Integrative Sciences, 2023)
This study aims to determine the effectiveness of using the talaqqi method to improve the memorization of the Qur'an in early childhood at Permata Kasih PAUD Kotabaru Cikampek. Because this research is motivated by the lack of children's ability to memorize the Al-Qu'an and because the method used is less attractive to children so that the learning process in memorizing the Al-Qur'an is less effective, then it is also because children carry out memorization in just a week only two or three times, so many children still forget their memorization. Furthermore, the method used is the talaqqi method. This study used a quantitative approach with an experimental method, a pre-experimental research design with the type of one group pretest-posttest design. In this study the population was all children at Permata Kasih PAUD consisting of 2 locales with a total of 25 children, of which the sample was group B consisting of 12 children. Thus, seen from the research results of students, it is very effective to use the talaqqi method in increasing Al-Qu'an memorization in early childhood